Interactive Visualization of Telegram - Choi, Jeong-Eun; Schäfer, Karla; Steinebach, Martin (Proceedings of the International AAAI Conference on Web and Social Media, 2026)
We present an interactive visualization for exploring a large-scale Telegram dataset. The demo primarily features (1) the interactive exploration of information flows between channels/groups and (2) a content analysis based on established NLP techniques. It demonstrates how diverse information extracted from complex, heterogeneous social media data can be integrated into a cohesive interface. The demo highlights the potential of technical tools to support interdisciplinary research, such as studies on disinformation, and provides users with interpretable insights for further analysis.